Analytical and clinical performance of the CDC real time RT-PCR assay for detection and typing of dengue virus. - Gilberto A Santiago; Edgardo Vergne; Yashira Quiles; Joan Cosme; Jesus Vazquez; Juan F Medina; Freddy Medina; Candimar Colón; Harold Margolis; Jorge L Muñoz-Jordán (Public Library of Science (PLoS), 2013)
Dengue is an acute illness caused by the positive-strand RNA dengue virus (DENV). There are four genetically distinct DENVs (DENV-1-4) that cause disease in tropical and subtropical countries. Most patients are viremic when they present with symptoms; therefore, RT-PCR has been increasingly used in dengue diagnosis. The CDC DENV-1-4 RT-PCR Assay has been developed as an in-vitro diagnostic platform and was recently approved by the US Food and Drug Administration (FDA) for detection of dengue in patients with signs or symptoms of mild or severe dengue. The primers and probes of this test have been designed to detect currently circulating strains of DENV-1-4 from around the world at comparable sensitivity. In a retrospective study with 102 dengue cases confirmed by IgM anti-DENV seroconversion in the convalescent sample, the RT-PCR Assay detected DENV RNA in 98.04% of the paired acute samples. Using sequencing as a positive indicator, the RT-PCR Assay had a 97.92% positive agreement in 86 suspected dengue patients with a single acute serum sample. After extensive validations, the RT-PCR Assay performance was highly reproducible when evaluated across three independent testing sites, did not produce false positive results for etiologic agents of other febrile illnesses, and was not affected by pathological levels of potentially interfering biomolecules. These results indicate that the CDC DENV-1-4 RT-PCR Assay provides a reliable diagnostic platform capable for confirming dengue in suspected cases.